2011
DOI: 10.1021/jp200562m
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Thermochemical Study of Barbituric Acids: Structure−Energy Relationship in 1,3-Dimethylbarbituric Acid

Abstract: This paper reports an experimental and computational thermochemical study on 1,3-dimethylbarbituric acid. The value of the standard (p° = 0.1 MPa) molar enthalpy of formation in the gas phase at T = 298.15 K has been determined. The energy of combustion was measured by static bomb combustion calorimetry, and from the result obtained, the standard molar enthalpy of formation in the crystalline state at T = 298.15 K was calculated as -639.6 ± 1.9 kJ·mol(-1). The enthalpy of sublimation was determined using a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
(45 reference statements)
2
10
0
Order By: Relevance
“…The heats of formation evaluated by M06-2X and CCSD(T) on the various CBH rungs are compared with the available experimental and calculated G3 values by Roux and co-workers in Table . It is readily observed that the CCSD(T) calculations at CBH-2 are in agreement with the Δ H f ° values obtained from G3 calculations by Roux et al The CCSD(T) calculations at CBH-2 yielded a value of −127.2 kcal/mol for the heat of formation for barbituric acid ( 1 ) against an experimental value of −127.8 kcal/mol . As seen in the cases of the aromatic amino acids, irrespective of the high reaction energies of the barbituric acid derivatives, the heats of formation with CCSD(T) are in excellent agreement with the experimental values as well as G3 calculations using the atomization schemes and the isodesmic schemes devised by Roux et al Similar observations are made for uracil and its derivatives 5 – 10 , where the CCSD(T) results at CBH-2 are in agreement with the experimental values and the G3 calculations on total atomization schemes for the uracil derivatives by Notario et al Similar to aromatic amino acids, we observe the M06-2X and CCSD(T) results to differ consistently by more than 2 kcal/mol and thus recommend the CCSD(T) results over M06-2X in such scenarios.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…The heats of formation evaluated by M06-2X and CCSD(T) on the various CBH rungs are compared with the available experimental and calculated G3 values by Roux and co-workers in Table . It is readily observed that the CCSD(T) calculations at CBH-2 are in agreement with the Δ H f ° values obtained from G3 calculations by Roux et al The CCSD(T) calculations at CBH-2 yielded a value of −127.2 kcal/mol for the heat of formation for barbituric acid ( 1 ) against an experimental value of −127.8 kcal/mol . As seen in the cases of the aromatic amino acids, irrespective of the high reaction energies of the barbituric acid derivatives, the heats of formation with CCSD(T) are in excellent agreement with the experimental values as well as G3 calculations using the atomization schemes and the isodesmic schemes devised by Roux et al Similar observations are made for uracil and its derivatives 5 – 10 , where the CCSD(T) results at CBH-2 are in agreement with the experimental values and the G3 calculations on total atomization schemes for the uracil derivatives by Notario et al Similar to aromatic amino acids, we observe the M06-2X and CCSD(T) results to differ consistently by more than 2 kcal/mol and thus recommend the CCSD(T) results over M06-2X in such scenarios.…”
Section: Resultssupporting
confidence: 82%
“…The 6-311++G(3df,2p) basis set was used for single-point calculations. CCSD(T)/6-311++G(3df,2p) energies were obtained by extrapolation. b The values were taken from refs where the G3 calculations were made using an atomization scheme. c Taken from ref . d Taken from ref . e Taken from ref . f Taken from ref . g Taken from ref . h Taken from ref . i Taken from ref . j Taken from ref . k Taken from ref . …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of a systematic study of the thermodynamic properties of this family of compounds and despite the important uses and applications of barbituric acid derivatives, reliable experimental thermochemical studies in literature are scarce . We have recently published thermochemical studies of the parent compound barbituric acid and its 5,5-dimethyl, 1,3-dimethyl, and 5,5-diethyl (barbital) derivatives. , We have also reported thermophysical studies of 2-thiobarbituric acid and some methyl and ethyl derivatives of barbituric acid …”
Section: Introductionmentioning
confidence: 99%